Computational paradigm techniques for enhancing electric power quality - Kumar, L. Ashok; Albert Alexander, S. (New York, NY : CRC Press/Taylor & Francis Group, 2019)
'The book provides the complete solution for the power quality improvement with intelligent techniques along with simulation exercises and experimental results. Apart from all the major verticals, it also provides the need of power quality improvement in renewable energy systems and implementation of power quality improvement practices'--
Includes bibliographical references and index.
Keywords: Electric power production -- Quality control -- Data processing